Evaluation of Residential Grid-Connected Photovoltaic System as the Potential Energy Source in Malaysia - S. S. Abd Wahid; Z. Nawawi; M. I. Jambak; Y. Z. Arief; M. A. B. Sidik; M. W. Mustafa; Z. Adzis (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexApplication of solar energy in Malaysia has been started in 1998. This country has a large potential of solar energy due to its location at equatorial region. The current energy consumption and demand in Malaysia is describes in this paper. The potential of solar energy in Malaysia is described together with the suitable photovoltaic construction. It also explains the plans conducted by Malaysia involving solar energy that covers investments and also projects involved such as Malaysia Building Integrated Photovoltaic (MBIPV). Simulation of grid-connected photovoltaic system in this study is performed using HOMER software. Finally, the potential of having a grid-connected PV system in a residential area is analyzed. The positive and negative findings in terms of cost and suitability of the system are explained.